Study of working conditions by dust factor in foundries with different production patterns - A. M. Lazarenkov; M. A. Sadokha; T. P. Kot; A. A. Novik (Литьë и металлургия, 2023)
The results of the dust content study at workplaces of foundry parts with different production patterns are considered. It is noted that the dust content in the foundry sections working area air exceeds the maximum permissible concentrations at all workplaces, while the greatest exceedances are noted in mass production workshops. The greatest impact of dust is exposed to the cutters, cleaners and casting technicians.